Blunted feedback processing during risk-taking in adolescents with features of problematic Internet use. (June 2015) - Yau, Yvonne H.C.; Potenza, Marc N.; Mayes, Linda C.; Crowley, Michael J.
Abstract: While the conceptualization of problematic Internet use (PIU) as a "behavioral addiction" resembling substance-use disorders is debated, the neurobiological underpinnings of PIU remain understudied. This study examined whether adolescents displaying features of PIU (at-risk PIU; ARPIU) are more impulsive and exhibit blunted responding in the neural mechanisms underlying feedback processing and outcome evaluation during risk-taking. Event-related potentials (ERPs) elicited by positive (i.e. reward) and negative (i.e. loss) feedback were recorded during performance on a modified version of the Balloon Analogue Risk Task (BART) among ARPIU ( n  = 39) and non-ARPIU subjects ( n  = 27). Compared to non-ARPIU, ARPIU adolescents displayed higher levels of urgency and lack of perseverance on the UPPS Impulsive Behavior Scale. Although no between-group difference in BART performance was observed, ERPs demonstrated overall decreased sensitivity to feedback in ARPIU compared to non-ARPIU adolescents, as indexed by blunted feedback-related negativity (FRN) and P300 amplitudes to both negative and positive feedback. The present study provides evidence for feedback processing during risk-taking as a neural correlate of ARPIU. Given recent concerns regarding the growing prevalence of PIU as a health concern, future work should examine the extent to which feedback processing may represent a risk factor for PIU, a consequence of PIU, or possibly both. Highlights: Examined relationship between ARPIU and ERPs related to feedback evaluation Attenuated ERP amplitudes among ARPIU adolescents during behavioral risk-task Attenuated ERP amplitudes suggest decreased sensitivity to feedback. Feedback-related ERPs (specifically FRN and P300) may serve as biomarkers for PIU.